ANALISIS KINERJA UNIT USAHA MENGGUNAKAN MODEL CCR (STUDI KASUS PADA APOTEK KIMIA FARMA SEMARANG) - Rahmania, Laily; Farikhin, Farikhin; Surarso, Bayu (MATEMATIKA, 2014)
Data envelopment analysis (DEA) is a non-parametric technique for performace evaluation. In DEA context, we know two model which are CCR model and BCC model. With these model we break all of decision making units (DMU) into two classess, efficiency DMU and inefficiency DMU. In this note, we discuss CCR model and its application to evaluate DMU’s on Kimia Farma Semarang. Further, we find that dual problem is better than primal problem to evaluate effiency DMU.